Association between Skin Color, Body Image, and Self-Esteem among Undergraduate Students: A Cross-Sectional Study - Suarilah, Ira; Laksono, Sindhu Agung; Asmoro, Candra Panji; Yusuf, Ah.; Fauzinintiyas, Rista (International Journal of Psychosocial Rehabilitation, 2020)
Living with lighter skin is the dream of most dark-skin youth. Younger people with dark skin probably experience dissatisfaction with the skin color which results in a less positive body-image and low self- esteem. This research aims to examine the relationship between skin color, body-image and self-esteem. The study design was a descriptive correlation with cross-sectional approach. A stratified random sampling technique was used and 211 respondents were included. The Independent variable was skin color; the dependent variables were body image and self-esteem. The variables were measured by Luschan skin color scales, Multidimensional Body- Self Relation Questionnaires (MBSRQ) and Rosenberg’s self-esteem scale (RSES). Data were analyzed using the Spearman Correlation statistic test. There was a correlation between skin color and body image (p = .000) and skin color and self-esteem (p = .015). Undergraduate students with dark skin who positively received their conditions presented positive body image and high self-esteem. Further research on the effects of peer, family, and society on the skin color associated with body image and self-esteem needs to be explored.